Radich Taisho corpus [data set] - Radich, Michael (Zenodo, CERN, 2022)
This packet provides the Taishō canon of Chinese Buddhist texts, as digitised by CBETA. The corpus has been modified by Michael Radich to reflect certain text-historical realities as understood by current scholarly consensus and/or the best current scholarship. The files have then been modified so that they can be used with the text-analysis tool TACL, or the TACL GUI. The corpus is described here. This corpus corresponds to the "full TACL Taisho database" (DOI: 10.5281/zenodo.6795219), also for use with TACL (and the GUI), which is available for download here.